Management of The COVID-19 Pandemic and Public Response in Lithuania: Knowledge, Attitudes, and Practices (KAP) - Genys Dainius; Krikštolaitis Ričardas (Baltic Journal of Law & Politics, 2022)
The article aims to provide an overview of the interrelationships between public knowledge, attitudes, and practical behaviours in the context of a global pandemic and the risk management measures used by the government. By reviewing some of the key trends in crisis management in Lithuania, it seeks to explore the response of society. The aim of the paper is to analyse the interrelationship among subjective public informativeness, attitudes, and behaviours according to different socio-demographic aspects. To meet the main objective of the paper, a representative public survey (N-804) on attitudes towards COVID-19 was conducted (at the end of 2020). The survey sought to explore individual self-protection measures, attitudes towards the dangerousness of the virus, the measures used by the government to combat the pandemic, and prevalent stereotypes and their implications on personal behaviour. The paper discusses the indicators, which are divided into separate blocks, on the basis of which the responses of the study participants are summed up and evaluated on a three-level (good, average, poor) rating scale, followed by correlation analyses on various socio-demographic parameters. The survey revealed that a higher proportion of Lithuanian society behaved responsibly, even being moderately informed and characterised by diverse attitudes.